Application of Hybrid Modified Differential Evolution and Pattern Search Optimization Techniques for Automatic Generation Control of Power System - Kumar Sahoo, Dillip; Kumar Sahu, Rabindra; Panda, Sidhartha (International Journal of Engineering and Technology, 2026)
A hybrid Modified Differential Evolution (MDE) and Pattern Search (hybrid MDE-PS) method is suggested in this paper for Automatic Generation Control (AGC) of two-area diverse source power system. The thermal, hydro and gas power plants are considered for each area of the power system. DE is applied with different strategies to tune the gains of the integral controller using an ITAE criteria. After that, variation in DE technique is suggested for the best strategy by altering two control parameters (step size and crossover probability) with an objective of attaining superior performance. Subsequently, PS technique is applied to fine tuning of the ultimate solution contributed by MDE. Additionally, various controller arrangement and modified objective function are proposed and the optimal controller parameters are obtained with suggested hybrid technique. Furthermore, variation in system parameters and loading conditions is being carried out for sensitivity analysis. From the result of sensitivity analysis, the robustness of the proposed scheme is established. Finally, suggested scheme has been expanded to a more practical system with the nonlinearities.